Peran E-Payment Terhadap Perilaku Konsumtif Generasi Z Dalam Bertransaksi di E- Commerce - Ginting Munthe, Rikawati; Ompusunggu, Vina Maria; Sinambela, Tiarmi (Universitas Quality, 2023)
Consumptive behavior is a phenomenon that affects people's lives today. Today's habits and lifestyles change rapidly in a relatively short time towards more luxury and excess, for example in terms of appearance which can lead to consumptive behavior. Researchers took the object of this research on generation Z, namely students whose births began in 1997-2000. The character of Generation Z is more diverse, global in nature, and has an influence on the culture and attitudes of most people. One thing that stands out, Generation Z is able to take advantage of technological changes in various aspects of their lives. Developments in the digital era make it very easy for consumers, especially tech-savvy generations, to easily obtain what they need in their daily lives. The use of E-Payment both for direct payments and the use of E-Commerce greatly answers the needs of today's younger generations and even more senior generations who do not want to be left behind in the use of technological advances. This study aims to look at the role of E-Payment on Consumptive Behavior in generation Z who likes to shop online at E-Commerce markets. The results of this study show the following results. First, the use of e-payment has a significant direct effect on consumptive behavior. This indicates that generation Z increases self-control in balancing the use of e-payments, so that e-payments can function as expected, which is able to facilitate student transactions, and avoid the bad side. Second, with self-control, generation Z as e- payment users can also avoid consumptive attitudes. Third, self-control is able to mediate between e- payment and consumptive behavior, thus if generation Z has high self-control, then the use of e- payment can suppress or reduce consumptive behavior in students. In that sense, students use e- payment only as needed. And there is an influence of E-Payment on the consumptive behavior of generation Z in transactions in E-Commerce by 16.7%.